2001
DOI: 10.2460/javma.2001.219.1732
|View full text |Cite
|
Sign up to set email alerts
|

Secondary hypoparathyroidism attributed to hypomagnesemia in a dog with protein-losing enteropathy

Abstract: Severe hypomagnesemia (0.8 mg/dl; reference range, 1.6 to 2.3 mg/dl), hypocalcemia, and protein-losing enteropathy were identified in a 5-year-old castrated male 3-kg (6.6 lb) Shih Tzu examined because of anorexia, lethargy, paresis, and abdominal distention. Histologic examination of intestinal biopsy specimens revealed lymphangiectasia and lymphocytic, plasmacytic, neutrophilic infiltrates. Initial treatment included administration of magnesium (0.80 mEq/kg [0.36 mEq/lb]) of body weight in a balanced electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…Several studies have described dogs with gastrointestinal disease and low total and iCa serum concentrations are often prone to hypocalcemia even after clinical improvement [9, 18, 19]. This could possibly be due to serum vitamin D levels not being corrected and/or increased fraction of serum ionized calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described dogs with gastrointestinal disease and low total and iCa serum concentrations are often prone to hypocalcemia even after clinical improvement [9, 18, 19]. This could possibly be due to serum vitamin D levels not being corrected and/or increased fraction of serum ionized calcium.…”
Section: Discussionmentioning
confidence: 99%
“…114 A prospective study of cats with diabetes mellitus or diabetic ketoacidosis (DKA) reported a point prevalence of ionized hypomagnesemia of 62% of diabetic and 57% of DKA cats. 27,83 The significance of these studies cannot be overlooked, and they lend strong support to the central concept that magnesium deficit in ill and hospitalized dogs and cats is common. 189 Interestingly, concurrent hypocalcemia and hypokalemia were documented in the majority of cats with magnesium deficiency in this study.…”
Section: Prevalence Of Magnesium Deficiencymentioning
confidence: 64%
“…Hypomagnesaemia has been reported in PLE cases10 and has been suggested to contribute to the development of an ionised hypocalcaemia state. Low magnesium may lead to a functional hypoparathyroidism as magnesium ions are required for successful exocytosis and release of PTH into the systemic circulation 10.…”
Section: Discussionmentioning
confidence: 99%
“…Low magnesium may lead to a functional hypoparathyroidism as magnesium ions are required for successful exocytosis and release of PTH into the systemic circulation 10. This can also have severe effects on calcium homeostasis and has been postulated to be an important contributor towards the hypocalcaemic state commonly observed in PLE patients.…”
Section: Discussionmentioning
confidence: 99%